Screams from the dark : 29 tales of monsters and the monstrous - Datlow, Ellen; Rogers, Ian, 1976-; Wilde, Fran, 1979-; Files, Gemma; Gregory, Daryl; Sharma, Priya; Hodge, Brian, 1960-; Oates, Joyce Carol, 1938-; Das, Indra; Carroll, Siobhan; Kadrey, Richard (Nightfire, 2022)
"Screams From the Dark is a chilling anthology featuring 29 all-original tales of monsters from bestselling and award-winning authors, edited by Ellen Datlow, one of the top editors in horror. From werewolves and vampires, to demons and aliens, the monster is one of the most recognizable figures in horror. But what makes something, or someone, monstrous? In Screams From the Dark, award-winning and up-and-coming authors like Stephen Graham Jones, Richard Kadrey, Cassandra Khaw, and Gemma Files attempt to answer this question. These stories run the gamut from traditional to modern, from mainstream to literary, from familiar monsters to the unknown and unimaginable. This bone-chilling collection has something to please-and spook-everyone, so lock your doors, turn off your lights, and try not to scream. Contributors include: Ian Rogers, Fran Wilde, Gemma Files, Daryl Gregory, Priya Sharma, Brian Hodge, Joyce Carol Oates, Indrapramit Das, Siobhan Carroll, Richard Kadrey, Norman Partridge, Garry Kilworth, Caitlín R. Kiernan, Chikodili Emelumadu, Glen Hirshberg, A. C. Wise, Stephen Graham Jones, Kaaron Warren, Livia Llewellyn, Carole Johnstone, Margo Lanagan, Joe R. Lansdale, Brian Evenson, Nathan Ballingrud, Cassandra Khaw, Laird Barron, Kristi DeMeester, Jeffrey Ford, and John Langan"--